Robust selenium-doped carbon nitride nanotubes for selective electrocatalytic oxidation of furan compounds to maleic acid. Issue 18 (8th April 2021) - Huang, Xin; Song, Jinliang; Hua, Manli; Chen, Bingfeng; Xie, Zhenbing; Liu, Huizhen; Zhang, Zhanrong; Meng, Qinglei; Han, Buxing
Abstract : Biomass-derived furan compounds could be selectively electro-oxidized into maleic acid over a robust selenium-doped carbon nitride nanotube catalyst. Abstract : Selective oxidation of biomass-derived furan compounds to maleic acid (MA), an important bulk chemical, is a very attractive strategy for biomass transformation. However, achieving a high MA selectivity remains a great challenge. Herein, we for the first time successfully designed and fabricated Se-doped graphitic carbon nitride nanotubes with a chemical formula of C3.0 N-Se0.03 . The prepared C3.0 N-Se0.03 was highly efficient for electrocatalytic oxidation of various biomass-derived furan compounds to generate MA. At ambient conditions, the MA yield could reach 84.2% from the electro-oxidation of furfural. Notably, the substituents on the furan ring significantly affected the selectivity to MA, following the order: carboxyl group > aldehyde group > hydroxyl group. Detailed investigation revealed that Se doping could tune the chemical structure of the materials ( e.g., C3.0 N-Se0.03 and g-C3 N4 ), thus resulting in the change in catalytic mechanism. The excellent performance of C3.0 N-Se0.03 originated from the suitable amount of graphitic N and its better electrochemical properties, which significantly boosted the oxidation pathway to MA. This work provides a robust and selective metal-free electrocatalyst for the sustainable synthesis of MA from oxidation of biomass-derived furan compounds.